Explor Neuroprot Ther 2021
DOI: 10.37349/ent.2021.00014
|View full text |Cite
|
Sign up to set email alerts
|

Blocking cholesterol storage to treat Alzheimer’s disease

Abstract: Cholesterol serves as an essential lipid molecule in various membrane organelles of mammalian cells. The metabolites of cholesterol also play important functions. Acyl-coenzyme A: cholesterol acyltransferase 1 (ACAT1), also named as sterol O-acyltransferase 1, is a membrane-bound enzyme residing at the endoplasmic reticulum (ER). It converts cholesterol to cholesteryl esters (CEs) for storage, and is expressed in all cells. CEs cannot partition in membranes; they can only coalesce as cytosolic lipid droplets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 77 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…There is emerging interest in targeting SOAT1, also known as acyl co-A cholesterol acyltransferase 1 (ACAT1), for neurological disorders [35,36] and recent work has shown that avasimibe may alleviate hepatocellular carcinoma [37,38]. Hence, considering our finding in this study, SOAT1 may be a plausible target for MASH and its progression.…”
Section: Discussionsupporting
confidence: 52%
“…There is emerging interest in targeting SOAT1, also known as acyl co-A cholesterol acyltransferase 1 (ACAT1), for neurological disorders [35,36] and recent work has shown that avasimibe may alleviate hepatocellular carcinoma [37,38]. Hence, considering our finding in this study, SOAT1 may be a plausible target for MASH and its progression.…”
Section: Discussionsupporting
confidence: 52%
“…For antiatherosclerosis treatment, several ACAT inhibitors have completed phase I safety trials ( 66 ). For treating NPCD, however, an important preclinical evaluation will be to test their brain permeability in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…ACAT enzymes are crucial components of cholesterol metabolism, and inhibition of their activity has great therapeutic potential, e.g., against hyperlipidemia, atherosclerosis, Alzheimer´s disease, Niemann Pick C disease, viral activity, and tumor growth [2,11,23,26,27,35,38,48,49,68,70,71]. For example, avasimibe, one of the most widely used ACAT inhibitors and a potent inducer of ACAT translocation in this study, has recently emerged as a promising anti-tumor compound [64,69,70,72].…”
Section: Discussionmentioning
confidence: 86%